Strain rate effect on twip/trip high entropy alloy - El Batal, Omar Mohammad Marwan (2021)
A Master of Science thesis in Mechanical Engineering by Omar Mohammad Marwan El Batal entitled, “Strain rate effect on twip/trip high entropy alloy”, submitted in July 2021. Thesis advisor is Dr. Wael Abuzaid and thesis co-advisor Dr. Maen Abdelqabder Alkhader. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).